Frustration and Anger in Games - Pierpaolo Battigalli; Martin Dufwenberg; Alec Smith (Center for Economic Studies and ifo Institute (CESifo), 2015)
Frustration, anger, and aggression have important consequences for economic and social behavior, concerning for example monopoly pricing, contracting, bargaining, traffic safety, violence, and politics. Drawing on insights from psychology, we develop a formal approach to exploring how frustration and anger, via blame and aggression, shape interaction and outcomes in economic settings.
Keywords: C72; D03; 330; frustration; anger; blame; belief-dependent preferences; psychological games